Colorants Pour Savon - National Aniline and Chemical Company
Eighteen soap samples, each colored with a different dye combination manufactured by the National Aniline and Chemical Company. Includes a description of the soap's composition and the method of dying.
Keywords: Dyes and dyeing; Dye industry; Soap; National Aniline and Chemical Company